Determinants of preterm infants' deaths at the Neonatal Intensive Care Units in the Northeast Countryside in Brazil - Raquel Gomes Lima; Verônica Cheles Vieira; Danielle Souto de Medeiros
Abstract Objectives: to assess preterm infants' characteristics, health conditions and neonatal care effect on their death at the neonatal ICU. Methods: this was a non-concurrent cohort study, including preterm infants from three neonatal ICUs from January 1st to December 31st, 2016, followed during the neonatal period and deaths registered during the entire hospitalization. Multivariate analysis was performed using Poisson regression. Results: of the 181 preterm infants, 18.8% died during hospitalization. Associated with the outcome: a gestational age between 28 and 32 weeks (RR= 5.66; CI95%= 2.08-15.40), and less than 28 weeks (RR=9.24; CI95%=3.27-26.12), Apgar score of 5th minutes less than 7 (RR: 1.82; CI95%=1.08-3.08), use of invasive mechanical ventilation up to 3 days (RR= 4.44; CI95%= 1.66-11.87) and 4 days and more (RR=6.87; CI95%=2.58-18.27). Besides the late sepsis (RR: 3.72, CI95%=1.77-7.83), acute respiratory distress syndrome (RR=2.86, CI95%=1.49-5.46), pulmonary hemorrhage (RR=1.97; CI95%=1.40-2.77), and necrotizing enterocolitis (RR= 3.41; CI95%=1.70-6.83). Conclusions: the results suggest the importance of using strategies to improve care during childbirth, conditions for extremely premature infants, early weaning from a mechanical ventilation and prevention on nosocomial infection.